Heterotopic pancreatic tissue in gall bladder incidentally detected in a case of acute cholecystitis: A case report and review of the literature - Mishra, Gaurav; Galande, Sneha; Sethna, Kaiumauz Sohrab; Mahajan, Pravin; Patil, Adwait; Venkateswaran, Vaidehi (Indian Journal of Case Reports, 2022)
Heterotopic pancreatic tissue in the gall bladder is a very uncommon lesion. In most cases, it is an incidental finding. The placement of pancreatic tissue in an organ outside the pancreas is called pancreatic heterotopy. Heterotopic pancreas is commonly found in the stomach, small intestine, and Meckel’s diverticulum. It has rarely been seen in the gall bladder, bile duct, splenic hilum, or liver. We present a case of incidentally discovered heterotopic pancreatic tissue in a case of acute cholecystitis in a 63-years-old lady having a history of pain in the right hypochondriac region.